Preopening and Equilibrium Selection - Riccardo Calcagno; Stefano Lovo (Tinbergen Institute, 2010)
We introduce a form of pre-play communication that we call preopening. During the preopening, players announce their tentative actions to be played in the underlying game. Announcements are made using a posting system which is subject to stochastic failures. Posted actions are publicly observable and players payoffs only depend on the opening outcome, i.e. the action profile that is posted at the end of the preopening phase. We show that when the posting failures hit players idiosyncratically all equilibria of the preopening game lead to the same opening outcome that corresponds to the most sensible pure Nash equilibrium of the underlying game. By contrast preopening does not operate an equilibrium selection when posting failure hits players simultaneously.
Keywords: C72; C73; C78; G1; 330; Preopening; equilibrium selection; bargaining; cheap talk; Nash-Gleichgewicht; Nichtkooperatives Spiel; Verhandlungstheorie